OPTIMASI HYBRID INTELLIGENT SYSTEM UNTUK IDENTIFIKASI BUAH: STUDI KASUS PISANG DAN APEL (INTI Nusa Mandiri, 2025)
Image processing-based fruit classification is one of the rapidly developing technology applications in the field of digital agriculture. This study aims to develop a fruit identification system, especially yellow bananas, green bananas, and apples, by utilizing the K-Nearest Neighbors (KNN) and Principal Component Analysis (PCA) methods. The background of this study is the need for an accurate automatic system to distinguish fruit types based on visual characteristics, such as color, texture, and shape, to support the distribution and management of agricultural products. The method used in this study involves four main stages: image loading, segmentation, feature extraction, and classification. PCA is used to reduce data dimensions by maintaining relevant main features, while KNN functions for classification based on the closest distance between test data and training data. The dataset used consists of 130 images, with 120 images as training data and 10 images as test data. The results of the study show that the developed system is able to classify all test data with 90% accuracy. This success proves that the combination of PCA and KNN methods is effective in identifying fruit types based on extracted visual characteristics. This system is expected to be the basis for further development in the field of automatic fruit classification.
Keywords: fruit classification; KNN; PCA